Characterization of the complete mitochondrial genome sequence of Tanichthys albiventris and phylogenetic analysis. Issue 2 (1st February 2023) - Yang, Tiezhu; Tan, Chenxi; Sun, Wenhao; Li, Dongpu; Zhao, Liangjie; Li, Fan
Abstract: In this study, we sequenced, annotated, and characterized the mitogenome of Tanichthys albiventris for the first time. The complete mitogenome is 16, 544 bp in length, consisting of 13 protein-coding genes (PCGs), 22 transfer RNA genes, and two ribosomal RNA genes. We found nine genetic overlaps and 17 intergenic spacer regions throughout the mitogenome of T. albiventris . The A + T content of the mitogenome is 60.93%. All PCGs have the same start codon of the standard ATG, excepting for that of cytochrome c oxidase 1 ( cox1 ) which is the GTG. A phylogenetic analysis with another 15 species of the Cyprinidae was performed using MrBayes and IQtree, based on the amino acid sequences of 13 mitochondrial PCGs. The results indicated that T. albiventris shares a close ancestry with Tanichthys albonubes .